An in vitro microleakage study of class V cavities restored with a new self-adhesive flowable composite resin versus different flowable materials - Mostafa Sadeghi (Wolters Kluwer Medknow Publications, 2012)
Background: Regarding the importance of sealing ability of restorative dental materials, this study was done to assess the microleakage of class V cavities restored with a new self-adhesive flowable composite resin and compare to different flowable materials. Materials and Methods: Seventy standardized class V cavities were prepared on the buccal surface of maxillary premolars teeth. The occlusal and the gingival margins of the cavities were located on the enamel and cementum/dentin, respectively. Teeth were randomly assigned into five groups (n = 14) and restored with different flowable materials following the manufacturer's instructions: groups I and II: EMBRACE WetBond flowable composite resin with and without acid etching and bonding agent, respectively; group III: flowable compomer (Dyract Flow); and IV and V: microhybrid (Tetric Flow) and nanofilled (Premise Flowable) flowable composite resins, respectively. After finishing and polishing, the teeth were stored in distilled water at 37°C, thermocycled, coated with nail varnish, and immersed in a basic fuchsin, and then longitudinally sectioned. Dye penetration was examined with a stereomicroscope and scored separately for occlusal and gingival on a 0-3 ordinal scale. Data were analyzed with Kruskal-Wallis, Mann-Whitney and Wilcoxon tests (α=0.05). Results: EMBRACE WetBond with acid etching and bonding agent had significantly less microleakage at the occlusal margins than those without, but not at cervical margins. Also cavities restored with EMBRACE WetBond without acid etching and bonding agent showed significantly greater microleakage scores than other groups at occlusal margin, but there was no significant difference at the cervical margin. Conclusion: The application of acid etching and bonding agent with EMBRACE WetBond provided better occlusal marginal sealing than those without at class V cavities.